2017
DOI: 10.11591/ijeecs.v6.i1.pp97-103
|View full text |Cite
|
Sign up to set email alerts
|

Optical Humidity Sensor Based on Tapered Fiber with Multi-walled Carbon Nanotubes Slurry

Abstract: We demonstrated performance comparison of optical humidity sensor for bare and Multi-walled carbon nanotubes (MWCNTs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…More recently, Mohamed et al further studied the evanescent field humidity sensor based on tapered single mode fiber with 6 µm of waist diameter, which was coated with multiwalled carbon nanotubes (MWCNTs) slurry. The experiment results demonstrated that the reported sensor can be used to measure relative humidity in the range of 45% to 80% at a constant room temperature, and the improvement of sensitivity from 3.811 µW/% of bare tapered fiber to 5.17 µW/% for the coated tapered fiber with (MWCNTs) slurry were observed.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Mohamed et al further studied the evanescent field humidity sensor based on tapered single mode fiber with 6 µm of waist diameter, which was coated with multiwalled carbon nanotubes (MWCNTs) slurry. The experiment results demonstrated that the reported sensor can be used to measure relative humidity in the range of 45% to 80% at a constant room temperature, and the improvement of sensitivity from 3.811 µW/% of bare tapered fiber to 5.17 µW/% for the coated tapered fiber with (MWCNTs) slurry were observed.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…As a result, the humidity concentration can be deduced by monitoring the variations of optical signals. In recent years, the development of the studies on microfiber humidity sensors have reached a flourish stage, many forms of MF humidity sensors have been developed, such as Sagnac loop interferometer, U‐shaped microfiber interferometers, microfiber couplers (MFCs), microfiber loop (knot) resonator, microfiber grating and tapered structure . Compared with different humidity sensors based on the structure of tapered, the fiber grating, the coupler or the resonator and the interferometer, the results show that the tapered–based RH sensor is directly utilizing a microfiber to measure the humidity, so it shows a simple structure and low cost, but this method makes them easily susceptible to fluctuations of optical source and fiber loss.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interaction between water molecules and the CNTs coating, the effective refractive index surrounding the core will change, resulting in a shift of the Bragg wavelength and a sensitivity of 31 pm/%RH within a linear detection range from 20-90 %RH. Mohamed et al [148] prepared an optical microfiber coated with MWCNTs slurry using the drop-casting technique. The fabricated sensor demonstrated a linear detection range from 45 to 80 %RH and an improvement of 1.3 times (5.17 µW/%RH) when compared to a bare tapered fiber.…”
Section: Humiditymentioning
confidence: 99%
“…The measured results obtained from the rGO/PS-coated optical microfiber exhibited a sensitivity of −0.224 dB/%RH and −4.118 dB/%RH for detection range 50.5-70.6 %RH and 79.5-85 %RH, correspondingly. Overall, Table 3 summarizes all carbon allotrope-based RH OFS and their respective sensing performance [134,[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162].…”
Section: Humiditymentioning
confidence: 99%
“…Additionally, non-uniform sensor structures, such as the Fabry-Perot cavity [ 7 ], fiber taper [ 8 ], micro-nano fiber [ 9 ], side-polished fiber [ 10 ], and U-bent fiber [ 11 ], are fragile and unfit for mass production [ 12 , 13 , 14 , 15 , 16 ]. Moreover, the combination of the functional materials and fiber sensors shows non-uniformity and uncertainty as well, especially when it comes to graphene oxide [ 17 ], metal oxide [ 18 ], UV gels [ 19 ], and nanoparticles [ 20 ]. For practical applications, fiber Bragg grating (FBG) combined with polymer provides a better way due to its long service and uniformity in mass production.…”
Section: Introductionmentioning
confidence: 99%